Effect of motivation and work patterns on performance through incentive intervention at Pertamina IHC clinic - Meilani, Desi; Nawasiah, Nana; Wicaksana, Seta A. (Universitas Widya Mataram, 2025)
This study aims to analyze the influence of motivation and work patterns on employee performance with incentives as an intervening variable for employees at the Pertamina IHC Clinic. The background of the study is based on the importance of improving employee performance in facing the demands of competitive healthcare services, where individual motivation and work pattern arrangements are believed to play a significant role. This study uses a quantitative approach with a survey method through questionnaires distributed to a number of employees as respondents. Data were analyzed using Structural Equation Modeling (SEM) or Partial Least Square (PLS) techniques to test direct and indirect relationships between variables. The results show that motivation and work patterns have a significant positive effect on employee performance. Incentives are only proven to play a role as an intervening variable that strengthens the relationship between work patterns and performance. This finding emphasizes the importance of human resource management strategies that not only pay attention to internal factors (motivation) and work systems (work patterns), but also strengthen them through the provision of appropriate incentives.